Facial identification of emotions: utility in bodies and security forces (local police) - Anta, Juan Ángel (2017)
This research is aimed at assessing if, with appropriate training, police can improve the identification of emotions expressed facially by a person versus those participants who do not receive any training. For this study we have included 11 emotions (7 basic and  4 new ‘added’) in order to identify if the 4 new ‘added’ emotions are detected in the same proportion as the basic ones.The results show that adequate training in facial identification of emotions substantially improves the cops’ ability to read facial expressions or any other non-verbal behavior. However, it would be interesting to delve into the overall formation of communication (verbal, paraverbal, facial and body) and not only in the facial in order for police to have more and better knowledge in verbal communication that is applicable practice in their functions as representatives of the law.